Maternal cardiovascular dysfunction in women with early onset preeclampsia: a cross-sectional study. (12th December 2022) - Pillai, Ajith Ananthakrishna; Thiyagarajan, Monica; Sharma, Devendra Kishanlal; Pant, Bhagwati Prasad; Keerti Priya, S. B.; Keepanasseril, Anish
Abstract: Background: Cardiac remodeling and diastolic dysfunction may occur, in women with early-onset preeclampsia, following raised total vascular resistance in response to the impaired placentation. These changes can increase the risk of premature cardiac morbidity and mortality later in life. According to updated guidelines by the American and European Societies of Echocardiography (ASE/ESE) to diagnose diastolic dysfunction, using a simpler criterion is not yet used in pregnant women. Objective: To compare the maternal cardiovascular changes and the variation in the diastolic dysfunction using the 2009 and 2016 criteria by ASE/ESE among women with early onset preeclampsia and gestational age-matched normotensive controls. Methods: A prospective matched cross-sectional study conducted in a tertiary hospital in South India, involving 40 women with early and 40 women with gestational age-matched normotensive controls. Cardiac function and remodeling were assessed by conventional 2D, M-mode, and Doppler echocardiography. Results: Compared to the controls, women with early-onset preeclampsia had significantly higher. Total vascular resistance index (2867.6 vs. 2277.2 dynes/s/cm 5 /m 2, p = .035) and median end-systolic stress index (5.2 vs. 9.2 dyne/cm 2 /m 2 ), suggesting a higher afterload. Cases had a significant rate of left ventricular diastolic dysfunction using the 2009 criteria (grade II/III: 21 (52%) vs. 0 (0%), p <.001) whereas the rates were much lower when the updated 2016 guidelines were used (grade II/III: 9 (22.5%) vs. 1 (2.5%), p <.001). Conclusions: In women with early-onset preeclampsia, cardiovascular adaption occurs to minimize wall stress and myocardial oxygenation. The prevalence of diastolic dysfunction was observed to be lower with the 2016 criteria. Further studies involving pregnant women are required to assess the impact of newer guidelines on association with short- and long-term cardiovascular outcomes in high-risk women.